"Statistical Optimization of Capric Acid Treatment on Cotton Fabric for Thermo-Regulating Finish to Produce Thermo-Tropic Smart Furnishing Textiles". Issue 9 (2nd September 2022) - Pal, Ayan; Samanta, Ashis Kumar; Kar, Tapas Ranjan
ABSTRACT: The present paper describes the treatment of 100% Cotton woven fabric with Capric acid (CA) as phase-change material (PCM) for imparting thermo-regulating finish with Hydroxy-Methyl-Poly-Siloxane (HMPS) binder to produce thermo-tropic "Smart textile, " which will act as a thermal barrier and restrict the flow of heat in case of external temperature fluctuation. Preliminary experiments for CA treatment on the cotton fabric were carried out by varying CA concentration, curing time, and curing temperature. CA-treated Cotton fabric was characterized by measurement of important physical properties like Tenacity with its CV%, Elongation %, Water vapor transmission, and Air permeability. The study was carried out for thermal behavior at 0–100°C by Cryogenic DSC, a surface appearance by SEM, functional groups by FTIR, and thermal decomposition pattern at a higher temperature. From the results of the preliminary experiments with the treatment of cotton fabric with CA in presence of HMPS, the three important input process variables were identified as (i) CA concentration, (ii) Curing time, and (iii) Curing temperature (keeping other input variables constant) for statistical optimization by Box-Behnken experimental design at three levels of variation generating suitable regression equation by response surface methodology for prediction of desired two important output/response parameters, i.e., (i) Water vapor transmission rate and (ii) Melting enthalpy value. It is found that optimum result was obtained by the use of 4% CA concentration in presence of 2% HMPS with 4 min curing time at 120°C curing temperature.